2017
DOI: 10.1038/sigtrans.2017.22
|View full text |Cite|
|
Sign up to set email alerts
|

Angiotensin type 2 receptor activation promotes browning of white adipose tissue and brown adipogenesis

Abstract: Brown adipose tissue dissipates energy in the form of heat. Recent studies have shown that adult humans possess both classical brown and beige adipocytes (brown-like adipocytes in white adipose tissue, WAT), and stimulating brown and beige adipocyte formation can be a new avenue to treat obesity. Angiotensin II (AngII) is a peptide hormone that plays important roles in energy metabolism via its angiotensin type 1 or type 2 receptors (AT1R and AT2R). Adipose tissue is a major source of AngII and expresses both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
73
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(82 citation statements)
references
References 65 publications
7
73
1
1
Order By: Relevance
“…Interestingly, AT 1 R receptor deletion suppresses in vitro adipocyte differentiation, with reduced expression of thermogenic genes. These data indicate that both receptors are involved in the regulation of adipogenic differentiation and likely the initiation of AT 2 R‐dependent activation of PI3‐kinase/Akt and AMPK signalling cascades and downregulation of ERK1/2 phosphorylation requires the formation of a heteromeric complex with AT 1 R . Furthermore, AT 2 R, acting as a partner for heterooligomerisation with β‐adrenoceptors, may exert additional indirect effects on WAT browning.…”
Section: At2r Heteromerisation and Signalling Determines Adsc Differementioning
confidence: 87%
“…Interestingly, AT 1 R receptor deletion suppresses in vitro adipocyte differentiation, with reduced expression of thermogenic genes. These data indicate that both receptors are involved in the regulation of adipogenic differentiation and likely the initiation of AT 2 R‐dependent activation of PI3‐kinase/Akt and AMPK signalling cascades and downregulation of ERK1/2 phosphorylation requires the formation of a heteromeric complex with AT 1 R . Furthermore, AT 2 R, acting as a partner for heterooligomerisation with β‐adrenoceptors, may exert additional indirect effects on WAT browning.…”
Section: At2r Heteromerisation and Signalling Determines Adsc Differementioning
confidence: 87%
“…AngII is consisted of AT1R and AT2R receptors, AT1R mainly conducted cell proliferation and smooth muscle contraction, while AT2R mainly modulates cell apoptosis and smooth muscle relaxation [23]. It has been reported that AngII is mediated in various diseases, such as renal disease [24], energy metabolism [25], and myocardial disease [26]. The previous study identified that AngII is involved in angiogenesis [27].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the relationship between AT2R and AMPK extended mainly in adipose tissue and lungs. One investigation revealed that in white adipocytes, AT2R may activate AMPK independent of AngII [119]. AT2R induced white adipocyte browning by increasing peroxisome proliferator-activated receptor (PPARγ) expression in primary cultures of mouse white adipocytes, which at least partially passes through AMPK, PI3k/Akt and ERK1/2 signaling pathways [119].…”
Section: At2r and Ampkmentioning
confidence: 99%
“…One investigation revealed that in white adipocytes, AT2R may activate AMPK independent of AngII [119]. AT2R induced white adipocyte browning by increasing peroxisome proliferator-activated receptor (PPARγ) expression in primary cultures of mouse white adipocytes, which at least partially passes through AMPK, PI3k/Akt and ERK1/2 signaling pathways [119]. Another research demonstrated that AngII adjusts the relationship of AMPKβ1/2 between Cdk4, leading to the hyperphosphorylation of retinoblastoma protein (Rb) and induction of E2F1(E2F is a group of genes that encodes a family of transcription factors in higher eukaryotes, E2F1 is one activator of the family)-dependent Bim gene activation in pulmonary artery endothelial cells (PAECs) [120,121].…”
Section: At2r and Ampkmentioning
confidence: 99%